2014
DOI: 10.1128/jb.02080-14
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Dependent Binding of Langerin to SodC, a Cell Wall Glycoprotein of Mycobacterium leprae

Abstract: M ycobacterium leprae infections lead to human leprosy, characterized by disfiguring skin lesions, nerve damage, and eventually permanent disability (1). As part of the disease process, M. leprae is phagocytized by numerous cell types, including dendritic cells (DCs) and epidermal DCs known as Langerhans cells (LCs) (2-4). The cell envelopes of pathogenic Mycobacterium spp., including M. leprae, are rich in mannosylated macromolecules such as mannose-capped lipoarabinomannan (ManLAM), lipomannan (LM), phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As LCs express very few Toll‐like receptors, the interaction of LCs with foreign molecules may be mainly through other receptors, for example, C‐type lectin receptors. It has been shown that Langerin binds HIV as an endocytic receptor and Langerin can also bind other microbes, such as Mycobacterium leprae and measles virus . Here, we showed that Langerin could bind a foreign protein, OVA.…”
Section: Discussionmentioning
confidence: 66%
“…As LCs express very few Toll‐like receptors, the interaction of LCs with foreign molecules may be mainly through other receptors, for example, C‐type lectin receptors. It has been shown that Langerin binds HIV as an endocytic receptor and Langerin can also bind other microbes, such as Mycobacterium leprae and measles virus . Here, we showed that Langerin could bind a foreign protein, OVA.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, the binding affinity of PGLI-M3 to serum antibodies measured by SPR was almost 30-fold lower than that measured by a solution binding assay (ELISA), in which the SPR technology was able to detect antibodies with just as few as 0.03 µg of the peptide, while ELISA required 1 µg per reaction. It is important to note that the versatility of the SPR platform has allowed not only the evaluation of peptide ligands to mycobacteria (Ngubane et al, 2013), but also has been used as immunosensors for hepatitis (Villiers et al, 2015) or for detection of salivary proteins (Musso et al, 2015), and also for characterization of binding affinity of human proteins to M. leprae glycoproteins (Kim et al, 2015). Another advantage of this platform is the possibility to transform angular variations in absolute values, which present greater application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is possible to obtain small peptides that mimic specific antigen epitopes (Goulart et al, 2010), or develop biomarkers using Fab (fragment antigen-binding) or scFv (single-chain variable fragment) antibody fragments (Leow et al, 2014). One of the great advantages of peptides and antibodies obtained by PD is their flexibility to be used in different diagnostic platforms, from conventional enzyme-linked immunosorbent assay (ELISA) (Rojas et al, 2014) to biotechnological platforms, such as those involving immunosensors based on surface plasmon resonance (SPR) (Kim et al, 2015). SPR immunosensors explore the capacity of an antibody to recognize its antigen with different affinities and can be built using an optical signal transduction by a light bean that passes through a prism and reaches a metallic surface (Kretschmann, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, M. leprae is the causative agent of leprosy, a chronic infectious disease. 8,22 M. leprae is phagocytized by numerous cell types; monocytederived macrophages are one of the most abundant host cells to come in contact with the mycobacteria. 23 The backbone of current treatment of leprosy is a multidrug therapy consisting of dapsone (DAP), clofazimine, and rifampicin as first-line drugs.…”
Section: Introductionmentioning
confidence: 99%